Al Qasimi Foundation 2013
DOI: 10.18502/aqf.0107
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Perceptions in Male Secondary School Dropouts in the United Arab Emirates

Abstract: The impact of socioeconomic status, family, and school experiences on the school continuation decision has been well-documented in Western literature. To date, however, no empirical studies have been conducted on the Gulf region. Using a sample of 149 dropouts and 347 non-dropouts, this study is the first to apply a mixed-methods comparative design to explore the patterns and trends in male dropout rates across government schools in the United Arab Emirates (UAE). Importantly, the study finds that the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In local student retention studies, Daleure (2011) completed a study of 294 male Emirati students at a HCT college and found that the key persistence factors at college were parental support, students' own dreams of continuing education, and the perceived quality of post-secondary education institutions within the UAE vis-à-vis study opportunities abroad; this supports many of Tinto's findings. Ridge et al (2013) found that the process of dropping-out from government schools in the UAE is associated with low socio-economic background, poorly educated and/or uninvolved parents, and de-motivating school experiences marked by unsupportive teachers and disruptive peers.…”
Section: Student Retentionmentioning
confidence: 99%
“…In local student retention studies, Daleure (2011) completed a study of 294 male Emirati students at a HCT college and found that the key persistence factors at college were parental support, students' own dreams of continuing education, and the perceived quality of post-secondary education institutions within the UAE vis-à-vis study opportunities abroad; this supports many of Tinto's findings. Ridge et al (2013) found that the process of dropping-out from government schools in the UAE is associated with low socio-economic background, poorly educated and/or uninvolved parents, and de-motivating school experiences marked by unsupportive teachers and disruptive peers.…”
Section: Student Retentionmentioning
confidence: 99%
“…Buckner’s (2018) analysis of the UAE’s 2015 PISA scores prompted a call for a learning focus that capitalizes on male interests and fostering a warm and welcoming environment where boys are physically and emotionally secure. Safety in schools and classrooms remains an issue, with cases of bullying not only found in student populations, but with and between teachers as well as parents (OECD, 2016, 2020; Ridge et al, 2013).…”
Section: Recommendationsmentioning
confidence: 99%
“…Factors related to individuals that could lead to dropout relate to characteristics and experiences both within and outside the school. They include such factors as student's academic achievements, retention, absenteeism, participation, and engagement in school activities, being motivated and social interaction with peers (Ridge et al, 2013;Abilgaziyeva et al, 2018). However, within the context of the individual learner, poor academic achievement has been found to be the strongest factor determining the student's intention to remain in school or to quit (Lee & Burkam 2003;Ahmad & Ahmad, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%